PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PELANGGAN DOMINO'S PIZZA PAMULANG BARAT - Syifana Khansyana Nur Fatimah, - (2019)
This research is quantitative research that aims to find out the influence of the product quality and service qualit to customer loyalty through the customer satisfaction as an intervening variable. The population in this research is RW 04 West Pamulang urban village. The sample size was taken by 75 respondents, with non probability sampling method, spesifically purposive sampling. Data collection was done through questionnaire distribution. Analytical technique used is the method of analysis PLS (Partial Least Square). The results of this study indicate that (1) product quality has a significant influence on customer loyalty with the coefficient value 0,180. (2) product quality has a significant influence on customer loyalty through satiscaction with the coefficient value of 0,385. (3) service quality has no significant influence on customer loyalty with the coefficient value of -0,025. (4) service quality has no effect on customer loyalty through satisfaction as intervening variable with coefficient value 0,113. (5) satisfaction has a significant influence customer loyalty with coefficient value of 0,757.